Đánh giá tình hình sản xuất, tiêu thụ cá tra năm 2021 và đề xuất nhiệm vụ, giải pháp năm 2022 - Nguyễn Anh Thư (2022)
|Đánh giá tình hình sản xuất, tiêu thụ cá tra năm 2021 và đề xuất nhiệm vụ, giải pháp.